Pengembangan Sistem Penggajian Pada CV. City Collection - Riezca Talita Trista (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
One of the most important assets to support a work program carried out at CV convection. City Collection is a payroll system. In the current process, it is certain that a company will produce a lot of work that requires quite a lot of employees to produce it. System development is one of the problem solvers that is reliable enough to develop a problem system in payroll transactions. In making the development of the payroll system using the Visual Basic 6.0 programming language as a database for data storage and using observation and interview methods using the Prorotype model. The application of the development of a payroll system that is supported by a desktop-based application which makes it an application that can make it easier for admins and financial officers in payroll, so that the level of effectiveness and efficiency of the employee's payroll system at convection City Collection has been reduced from before.